2022
DOI: 10.1186/s12882-022-02933-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in Turkey: epidemiological characteristics, etiology, clinical course, and prognosis

Abstract: Background This study aimed to evaluate the etiologies, comorbidities, and outcomes of acute kidney injury (AKI) in Turkey and determine any potential differences among different geographical parts of the country. Methods This prospective observational study was conducted by the Acute Kidney Injury Working Group of the Turkish Society of Nephrology. Demographical and clinical data of patients with AKI at the time of diagnosis and at the 1st week an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…A similar finding in a prospective study in a tertiary care center in China found that prerenal was the most frequent cause of AKI, occurring in 27.7% of the cases [ 42 ]. Researchers in a recent regional study in Turkey that included 776 patients diagnosed with AKI found that prerenal AKI was the most prevalent etiology with high exposure to nephrotoxic medication, similar to our finding [ 24 ]. Prerenal AKI occurs due to kidney hypoperfusion, which can be related to a decline in cardiac output volume and renal perfusion due to different conditions such as bleeding, severe vomiting or diarrhea, dehydration, or diuretic use.…”
Section: Aki Stagesupporting
confidence: 90%
See 1 more Smart Citation
“…A similar finding in a prospective study in a tertiary care center in China found that prerenal was the most frequent cause of AKI, occurring in 27.7% of the cases [ 42 ]. Researchers in a recent regional study in Turkey that included 776 patients diagnosed with AKI found that prerenal AKI was the most prevalent etiology with high exposure to nephrotoxic medication, similar to our finding [ 24 ]. Prerenal AKI occurs due to kidney hypoperfusion, which can be related to a decline in cardiac output volume and renal perfusion due to different conditions such as bleeding, severe vomiting or diarrhea, dehydration, or diuretic use.…”
Section: Aki Stagesupporting
confidence: 90%
“…Regional studies on AKI prevalence, risk factors, and settings are limited. A recent study in Turkey revealed that nephrotoxic drugs are the most common etiology of AKI with a 24% death rate after 6 months of diagnosis, and a study in Saudi Arabia on HA-AKI reported serious complications and minimal renal recovery [ 23 , 24 ]. To the best of our knowledge, no studies have been conducted in Palestine to explore this topic; therefore, this study aimed to evaluate the severity, risk factors, outcomes, and prevalence of CA-AKI and HA-AKI in patients diagnosed with AKI at tertiary care hospitals in Palestine.…”
Section: Introductionmentioning
confidence: 99%
“…The hospital-acquired AKI cases were 30-70% of critically ill patients originating from the ICU (9). In our study, out of 724 AKI cases that were reported from the centers, 126 (17%) originated from the ICU, 350 (48%) were inpatients (hospital acquired), and 248 (34% of them) were community acquired (10).…”
Section: Discussionmentioning
confidence: 58%
“…This was the subgroup analysis of a prospective observational study conducted by the Acute Kidney Injury Working Group of the Turkish Society of Nephrology (10). The data were collected through the web-based data program; this program was sent to all the centers in Turkey, and the ones who responded to our call were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…), whereas the cause of postrenal AKI is inadequate urinary drainage ( e.g ., kidney stones, abdominal or pelvic mass, prostatic disease). 8 , 9 Intrinsic AKI is caused by direct kidney damage that is the result of acute tubular necrosis, acute interstitial nephritis, and vascular diseases such as hemolytic uremic syndrome, vasculitis, and hypertensive emergencies, among others. 10 , 11 Clinically, different criteria are used to define AKI, including Risk, Injury, Failure, Loss of kidney function, and ESKD; AKI Network; and Kidney Disease Improving Global Outcomes (KDIGO); of the three, KDIGO is the one most commonly used in clinic.…”
Section: Clinical Overview Of Akimentioning
confidence: 99%